Oportunidades comerciales en el sector del cafe y sus derivados ante TLC con Estados Unidos (2023)
The objective of this monograph was to analyze the behavior that the leather goods sector in Colombia has presented with the commercial opening generated by the Free Trade Agreement with the United States, for which a qualitative study was carried out with a descriptive approach using of the bibliographic review as an instrument for collecting information. It was concluded that the levels of production, sales and employment have not shown a positive trend that could show a full benefit in the period studied. In relation to exports, which are the ones that bring the highest income and economic benefits to the country due to the fact that it is one of the largest producers in the world, they have not been very marked or high, maintaining an almost linear trend during the period studied, thereby denoting that the FTA has not generated contributions of significant impact. Therefore, a series of opportunities within the sector were designed taking advantage of said treaty, the excellent commercial link that has been had with the United States as well as the potential, qualities, diversity and characteristics of the sector. These opportunities are mainly focused on attending, on the one hand, the trends and interests of the American market, and on the other hand, taking advantage of the capacity, availability, quality and variety of Colombian coffee products.